Tetraspanins, Another Piece in the HIV-1 Replication Puzzle - Suárez, Henar; Rocha-Perugini, Vera; Álvarez, Susana; Yáñez-Mó, María (Frontiers in Immunology, 2018)
Despite the great research effort placed during the last decades in HIV-1 study, still some aspects of its replication cycle remain unknown. All this powerful research has succeeded in developing different drugs for AIDS treatment, but none of them can completely remove the virus from infected patients, who require life-long medication. The classical approach was focused on the study of virus particles as the main target, but increasing evidence highlights the importance of host cell proteins in HIV-1 cycle. In this context, tetraspanins have emerged as critical players in different steps of the viral infection cycle. Through their association with other molecules, including membrane receptors, cytoskeletal proteins and signalling molecules, tetraspanins organize specialized membrane microdomains called Tetraspanin-Enriched Microdomains (TEMs). Within these microdomains several tetraspanins have been described to regulate HIV-1 entry, assembly and transfer between cells. Interestingly, the importance of tetraspanins CD81 and CD63 in the early steps of viral replication has been recently pointed out. Indeed, CD81 can control the turnover of the HIV-1 restriction factor SAMHD1. This deoxynucleoside triphosphate triphosphohydrolase counteracts HIV-1 reverse transcription (RT) in resting cells via its dual function as dNTPase, catalyzing dNTPs into deoxynucleosides and inorganic triphosphate, and as exonuclease able to degrade single stranded RNAs. SAMHD1 has also been related with the detection of viral nucleic acids, regulating the innate immune response and would promote viral latency. New evidences demonstrating the ability of CD81 to control SAMHD1 expression, and as a consequence HIV-1 RT activity, highlight the importance of TEMs for viral replication. Here, we will briefly review how tetraspanins modulate HIV-1 infection, focusing on the latest findings that link TEMs to viral replication.